ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN KAJIAN LITERASI KEWIRAUSAHAAN PELAKU USAHA TANI PERKOTAAN DI KOTA MAKASSAR - Miranda Miranda; Muh Ihsan Said Ahmad; Muhammad Hasan; Nurdiana Nurdiana; Tuti Supatminingsih (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to determine the level of entrepreneurial literacy possessed by urban fariming entrepreneurs in the city of Makassar, especially in the Orchid Women Farmer Group located in the Bara-Baraya sub-district, Makassar district and the implementation of entrepreneurial literacy in agricultural activities. This study uses a qualitative approach with descriptive methods collected using three techniques namely observation, interviews, and documentation. Then to determine the sample in this study using the purposive sampling method with the provisions of criteria, namely: (1) joined in the Women’s Group of Orchid Farmers; (2) is an important part (top) in the organizational structure; (3) knows the ins and outs of the Women’s Group of Orchid Farmers so as to be able to provide information that can represent; (4) domiciled in the city of Makassar. After exploring, it was found the the Women’s Group of Orchid Farmers in general already have entrepreneurial literacy and knowledge releted to entrepreneurship has been implemented in their farming activities although it is not optimal because not all members have and understand entrepreneurial literacy. Keywords: entrepreneurial literacy, urban farmer, makassar city